- - Rivas M., Favio (Acta Bioethica, 2000)
Violence is still on the increase even though the world is no longer divided. With the fall of the Berlin wall most of us were expecting the end of wars, something that never happened. On the other hand, internal conflicts in the third world have become more and more frequent. Today, homicide is the first cause of death in Colombia, being men aged from 15 to 44 the principal victims. Violence is the major public health problem in Colombia nowadays. It is impossible to understand this issue from a unique point of view. To address this problem, as it occurs with Bioethics, inter-disciplinary actions must be taken. It is a phenomenon related to distributive justice and the autonomy of men and nation’s, in a context where the intention to inflict harm (maleficence) prevails. There exist, therefore, an enormous domain for bioethics, especially for those of us who deem necessary to remove it from its clinical atmosphere in order to collaborate in the searching for solutions to the urgent problems this side of the orld is facing.